Globalization for development : the international trade perspective (UN New YorkUS, 2008)
Profiles key trade and development issues that will have to be addressed in the years ahead in order to promote beneficial and inclusive globalization. Discusses the national, regional and international actions needed to create an enabling environment for development. Underscores that benefiting from globalization hinges on the effective integration of developing countries into the world economy and the international trading system, both in quantitative and qualitative terms.
Keywords: GLOBALIZATION